Research on the Method of Capitalization of Entertainment Products in GDP Statistics - Gong, Weiguang; Hu, Jiaojiao; Peng, Xiaobao; Li, Yang (Scientific Research, 2016)
It is one of directions of the reform about China’s national economic statistics system to incorporate the intellectual property products into the GDP statistics, and the capital of intellectual property products is the first work to be incorporated into the GDP statistics. This article selected the entertainment industry as a microcosm of the development of the intellectual property economic, and accounted the capitalization of the original expenditure on entertainment industry to provide a reference for Chinese intellectual property products capital accounting and GDP accounting system reform.
Keywords: GDP Statistics; Entertainment Industry; Capital Accounting Method